2020
DOI: 10.26858/jnp.v8i1.13666
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Status Sosial Ekonomi Orang Tua Dan Pendidikan Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa Di Universitas Negeri Makassar

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh status sosial ekonomi orangtua dan pendidikan kewirausahan terhadap minat berwirausaha mahasiswa di Universitas Negeri Makassar. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan korelasi. Teknik pengumpulan data dilakukan dengan observasi, wawancara, dokumentasi dan penyebaran angket (kuisioner). Populasi dalam penelitian ini sebanyak 360 mahasiswa Universitas Negeri Makassar yang menjadi peserta dan telah mengirimkan proposal Program Kreativi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Jailani's 2019 study confirms the influence of family socioeconomic position on the desire to become an entrepreneur. These results were unexpectedly different from the survey findings byIsma et al (2020), which revealed no conclusive relationship between parental socioeconomic status and student entrepreneurial ability.E. CONCLUSION 1.…”
contrasting
confidence: 99%
“…Jailani's 2019 study confirms the influence of family socioeconomic position on the desire to become an entrepreneur. These results were unexpectedly different from the survey findings byIsma et al (2020), which revealed no conclusive relationship between parental socioeconomic status and student entrepreneurial ability.E. CONCLUSION 1.…”
contrasting
confidence: 99%
“…Sedangkan sisanya sebanyak 3 mahasiswa tidak memiliki keinginan untuk menjalankan usaha. Namun keinginan tersebut rupanya masih keinginan yang belum disertai dengan aksi nyata (praktik) (Larasati, 2020…”
Section: Pendahuluanunclassified
“…Where the demands of globalization competition will color increasingly fierce labor competition, open job markets at the international level, increasingly fierce competition for the quality of human resources (HR) in all sectors of life, both the education sector and the industrial sector. The education sector has an important role in producing quality and skilled output or graduates, while the industrial Sector requires a productive workforce that can produce a particular product or service that can compete in the market.Wahyuningsih (2020), Suarjana and Wahyuni (2017), Isma et al (2020) which states that there is a significant effect of entrepreneurship education on student interest in entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%